The association of γδT lymphocytes with cystic leukomalacia in premature infants - Yuan, Mengjie; Jin, Xinyun; Qin, Fanyue; Zhang, Xiaoli; Wang, Xiaoyang; Yuan, Enwu; Shi, Ying; Xu, Falin (Frontiers in Neurology, 2022)
Background: Periventricular leukomalacia (PVL) is an essential cause of cerebral palsy in preterm infants, and cystic PVL (cPVL) is the most severe form of the disease. The pathogenesis of cPVL is complex, and immune imbalances and inflammatory responses may play an essential role in it. Objective: To investigate the correlation between peripheral blood lymphocyte subsets, especially γδT cells with the pathogenesis of cPVL in preterm infants. Methods: Peripheral blood from preterm infants with GA < 32 weeks and BW < 1500 g was used in this study, and were collected at 34 weeks corrected gestational age and within 24 hours after the diagnosis with cranial MRI or cranial ultrasound. The infants were divided into cPVL groups and control groups. Flow cytometry was used to detect peripheral blood γδT, CD3+, CD4+, CD8+ and the proportion of total lymphocytes. Multiplex cell assays was used to detect the concentration of extracellular serum cytokines IL-6, IL-2, IL-8, IL-17A, IL-10, and IFNγ. A follow-up visit was carried out when the patient was three years old. Results: After correcting for confounding factors, the proportion of peripheral blood γδT in the cPVL group was significantly lower than in the control group (β: 0.216; 95% CI: 0.058 0.800, P<0.022). Peripheral blood γδT (AUC: 0.722, P=0.006) and multivariate binary regression model (AUC: 0.865, P<0.000) have good diagnostic values for cPVL. Peripheral blood γδT has some predictive power for neurodevelopmental outcomes in preterm infants (AUC: 0.743, P=0.002). Conclusions: It seems that peripheral blood γδT cells are inversely correlated with cPVL, which is not only a risk factor for cPVL disease, but also for neurodevelopmental outcomes in preterm infants. However, the causality of cPVL and various lymphocytes is unclear and needs further study.